Pretreatment thrombocytosis as an independent predictive factor for chemoresistance and poor survival in epithelial ovarian cancer - Sari Nakao; Takeo Minaguchi; Hiroya Itagaki; Yoshihiko Hosokawa; Ayumi Shikama; Nobutaka Tasaka; Azusa Akiyama; Hiroyuki Ochi; Koji Matsumoto; Toyomi Satoh (BMC, 2020)
Abstract Background Thrombocytosis is related to tumor stage and survival in ovarian cancer in addition to the common complications of malignant diseases, such as anemia and inflammation. The aim of our study was to clarify the precise prognostic impact of pretreatment thrombocytosis in epithelial ovarian cancer. Methods We retrospectively analyzed 280 consecutive patients who were treated for epithelial ovarian cancer at our institution between 2001 and 2011. Results Pretreatment thrombocytosis was observed in 18.9% of all patients and was associated with advanced FIGO stage, primary treatment, operation achievement, histologic subtype, microcytic hypochromic anemia (MHA), and nonmalignant inflammatory condition (P = 0.0018, 0.0028, 0.00050, 0.034, 0.00090 and 0.0022). In the patients who relapsed after primary adjuvant chemotherapy (n = 126), thrombocytosis was associated with a shorter treatment-free interval (TFI) (P = 0.0091). The univariate and multivariate analyses revealed that thrombocytosis was independently associated with TFI and MHA (P = 0.021 and 0.0091). Patients with thrombocytosis had worse progression-free survival (PFS) and overall survival (OS) than those without thrombocytosis (P <  0.0001 and <  0.0001). The multivariate analyses for prognostic factors demonstrated that thrombocytosis was significant for poor PFS and OS (P = 0.0050 and 0.022) independent of stage, histology, primary treatment, operation achievement, nonmalignant inflammatory condition and MHA. Conclusions The current findings indicate that the detrimental survival impact of pretreatment thrombocytosis in epithelial ovarian cancer may be independent of tumor extent but rather attributed to chemoresistance, further supporting the therapeutic potential of targeting thrombopoietic cytokines in the disease.